Transcriptome analysis of Mesobuthus martensii revealed the differences of their toxins between females and males. Issue 1 (31st December 2022) - Yang, Y.; Zhu, Y.; Luo, Y.; Liu, Q.; Hua, X.; Li, J.; Gao, F.; Hofer, J.; Gao, X.; Xiao, L.; Song, X.; Gao, S.; et al.
Abstract: Scorpion venom plays an important role in scorpion predation, competition, communication, and defense. In this study, the species identification of Shandong scorpion and the analysis of venom extracted from male and female scorpion at the transcriptome level and their activity were compared. Whole de novo transcriptomes were performed on male and female scorpions and the sequences of cytochrome c oxidase subunit I were screened to identify the species. The scorpions collected were identified as Mesobuthus martensii and we have successfully annotated 16, 726 (37.47%), 10, 076 (22.57%), 10, 878 (24.37%), and 10, 187 (22.82%) unigenes with NR, Swissport, GO and KEGG database. A total of 17 kinds of toxins and 181 toxin-related unigenes were screened. There is no accurate identification of the differences between male and female scorpions at the molecular level and these need to be further explored. The difference ratio in toxins was 6.08%, and this number in unigenes was 0.78%. There are seventeen toxins and other toxins related genes were analyzed in male and female scorpions, among which the representative phospholipase, makatoxin toxin, and plancitoxin toxin were all related to the biological functions of scorpion martensii. EF chiral domain in phospholipase: helix turn helix is related to calcium channel toxin; The QWAKYGN base sequence contained in makatoxin toxin is α-toxin specific domain; It was found in plancitoxin I toxin that it contains two deoxyribonuclease II active sites, HEK, and DHSK. Since calcium channel toxins are associated with α- toxins belong to neurotoxins. Therefore, phospholipase and makatoxin are both toxins that act on the nervous system, while plancitoxin I toxin has deoxyribonucleotidase II activity and can degrade DNA in mammals. We constructed structure analysis including sequence alignment, 3D modeling, and phylogenetic analysis in phospholipase, makatoxin, and plancitoxin. There was little difference showed in GO and KEGG analysis and the differences ratio in unigenes annotated as toxins was much higher than that in all unigenes. What's more, the evaluation of toxin activity showed that the toxicity of female scorpion was likely to be higher than that of male scorpion. The method can be used as a useful tool to evaluate the difference between male and female animals.